A Comparative Analysis of Power Strategies Used by Voldemort and Grindelwald Over Their Followers Through Foucault’s Perspective - Bellinzha Graine Nurshifa; Devi Hellystia (CV. Rustam, 2025)
Power in the Wizarding World is never static; it seduces, coerces, and eventually collapses. This article examines the contrasting strategies of Lord Voldemort and Gellert Grindelwald in Harry Potter and the Deathly Hallows Part 1 and 2 and Fantastic Beasts: The Crimes of Grindelwald and The Secrets of Dumbledore through Michel Foucault’s framework of sovereign power, disciplinary power, biopower, governmentality, and resistance. Voldemort governs through terror and spectacle, enforcing obedience while fostering silent rebellion. Grindelwald, in contrast, wields ideology and charisma to secure loyalty, until coercion exposes the fragility of his control. As Foucault posits, power is relational and fluid, destined to provoke resistance. Beyond fantasy, these narratives reflect enduring truths about authority, its seductive nature, and its inevitable unravelling.